The assessment of the intra-annual runoff distribution of the northern slope Zhetysu Alatau rivers (Journal of Geography and Environmental Management, 2022)
The article presents the results of an assessment of the intra-annual runoff distribution of the northern slope Zhetysu Alatau rivers. Based on the data of recent years, the average monthly flow of rivers for different years of water content has been clarified, and their changes relative to earlier assessments are shown.The runoff series data of the hydrometeorological service network contain a large number of gaps in observations, in connection with that the hydrological series were reconstructed using the analogy and ratio method. As a validity control of the reconstruction of the series, the root-mean-square errors of the reconstructed series of monthly averages were calculated. To assess the intra-annual runoff distribution of the northern slope Zhetysu Alatau rivers, histograms of the distribution of runoff by months and seasons (as a percentage of the annual) were constructed for four water content groups: high-water, medium, low-water and very low-water for the period 1965-2019. A comparative analysis of the obtained results with the results of previous works, in particular, with the data of «Surface Water Resources of the USSR», where the average periods of the water regime phases are given according to data for 1930-1965 was carried out. The results of the analysis of indicators of the intra-annual runoff distribution in the region under consideration made it possible to identify characteristic features in runoff formation, changes relative to earlier assessments.
Keywords: average monthly runoff; series of observations; intra-annual runoff distribution; correlation coefficient; flood period